Geoinformation systems in the field of agricultural land use - Sharyi, G.; Nesterenko, S.; Gamernyk, D.; Tymoshevskyi, V. (Land Management, Cadastre and Land Monitoring, 2020)
Agribusiness conditions in Ukraine are changing. Agricultural enterprises are actively restructured, change owners, attract investors and crisis managers. Management technologies that are currently used by most Ukrainian agricultural enterprises do not allow effective management decisions and create development plans that require objective and expeditious asset valuation, analytically sound performance data. This problem can be solved by creating a unified agribusiness management system which is based on advanced analysis methods and modern information technologies.The necessity to create a database of the land bank of enterprises with the ability to export information to the corporate system of enterprise management has been proved. Taking into account a number of criteria such as complexity, functionality and correlation price and quality, the following solutions were selected that enabled the creation of a flexible, complete and versatile agribusiness management system with the ability to modify it depending on changing needs. It is suggested to pay additional attention to the developers and to develop in each direction a software product aimed at development in the broadest sense of the production and macroeconomic social phenomenon. It is not just a land bank management but a land development, and it should form a geoinformation characteristic of the spatial basis by section, by legal status and by legal entities. The aforementioned analysis will form a spatial picture of basic lands, natural and economic assessment, environmental sustainability (buffering), toxicity and potential natural and economic yield.The introduction of modern technologies increases the control of the assets of companies, the transparency of processes and information management, reduces the risks of doing business been proved.Keywords: information systems, agricultural production, management decisions, land resources.